2000
DOI: 10.1074/jbc.m000783200
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine Phosphatase Reduces the Number of Apical Small Conductance K+ Channels in the Rat Cortical Collecting Duct

Abstract: Previous studies have demonstrated that an increase in the activity of protein-tyrosine kinase (PTK) is involved in the down-regulation of the activity of apical small conductance K ؉ (SK) channels in the cortical collecting duct (CCD) from rats on a K ؉ -deficient diet (1). We used the patch clamp technique to investigate the role of protein-tyrosine phosphatase (PTP) in the regulation of the activity of SK channels in the CCD from rats on a high K ؉ diet. Western blot analysis indicated that PTP-1D is expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
8
40
0
1
Order By: Relevance
“…Furthermore, we have shown that ROMK1 was a substrate of PTK and that tyrosine phosphorylation of ROMK increased during K depletion and decreased by high K intake (15). The role of PTK in regulating ROMK channel activity in the CCD is further established by the observation that inhibition of PTK increases (1), whereas inhibition of protein tyrosine phosphatase decreases (20), ROMK channel activity. The inhibitory effect of PTK on ROMK1 is the result of stimulation of the ROMK internalization.…”
Section: Fig 10mentioning
confidence: 79%
“…Furthermore, we have shown that ROMK1 was a substrate of PTK and that tyrosine phosphorylation of ROMK increased during K depletion and decreased by high K intake (15). The role of PTK in regulating ROMK channel activity in the CCD is further established by the observation that inhibition of PTK increases (1), whereas inhibition of protein tyrosine phosphatase decreases (20), ROMK channel activity. The inhibitory effect of PTK on ROMK1 is the result of stimulation of the ROMK internalization.…”
Section: Fig 10mentioning
confidence: 79%
“…Purified human CG (hCG CR-127, potency 14 900 IU/mg) was a gift from Dr Parlow, National Hormone and Pituitary Program, NIDDK, NIH (Bethesda, MD, USA). Stimulations were performed in the presence or absence of phenylarsine oxide (PAO), a cell-permeable PTP inhibitor (García Morales et al 1990, Wei et al 2000, added to the cells 10 min before the stimuli. Following the appropriate treatments, MA-10 cells were placed in an incubator at 36 C and 5% CO 2 for the time periods indicated in the Figure legends.…”
Section: Conditions For Incubation Of Ma-10 Cells With Ptp Inhibitorsmentioning
confidence: 99%
“…We previously demonstrated that low K intake decreases the apical small-conductance K (SK) channel activity (6). The effect of low K intake on the SK channels is mediated by a protein tyrosine kinase (PTK)-dependent pathway (7,8) because inhibition of PTK increases the SK channel activity in the CCD (9,10). Moreover, we have shown that low K intake increases superoxide levels which mediate the effect of low K intake on PTK expression (6) and that suppression of superoxide production with tempol diminishes the effect of low K intake on c-Src expression (6).…”
mentioning
confidence: 99%